African cerebral vascular accidents, about 142 sightings - (:unkn) unknown (My University, 1961)
The cerebrovascular pathology in white is already well studied and every day better known. This problem "since the beginning of the anatomo-clinical era has not been the subject of careful research which has left little unexplored point.The imposing set of classic works crowned by the masterful work of Charles FOIX makes advance hesitating one who would tryto direct his steps on such broken things, said CASTA IGNE in 1957.On the other hand, the cerebrovascular pathology of the African was still poorly understood until recent years.In Black Africa, in fact, the problem is still almost complete, and this for various reasons:It was urgent to study other diseases of obvious social importance.The Pasteurian culture of physicians directed them towards the study of parasitic and infectious diseases.This orientation was, moreover, justified by the importance of these diseases.- Doctors had a spectator attitude towards the cerebral stroke and its complications, an attitude that was justified by the technical difficulties of exploration and the precariousness of the therapeutic means.- Many acute accidents escaped medical observation, either, because the patients died quickly,either, because they consulted after the failure of a local therapy.
Keywords: African Research